Asuhan Kebidanan Berkesinambungan pada Ny. T dengan Pemberian Aromaterapi Lavender untuk Mengurangi Nyeri Persalinan di Praktik Mandiri Bidan Hj. Zurrahmi - Prastika, Cindy Eka; Desi Nindya Kirana (JURNAL ILMIAH NUSANTARA, 2025)
Labor pain is a physiological problem experienced by 85-90% of mothers worldwide. In Pekanbaru, 68% of births require pain management. This Evidence-Based Practice (EBP)-based study aims to analyze the effectiveness of lavender aromatherapy in reducing labor pain integrated in the Continuity of Care (COC) model. This case study was conducted on Mrs. T, a 19-year-old primigravida, at the Independent Practice of Midwife Hj. Zurrahmi. Lavender aromatherapy interventions were administered through a diffuser during period I labor, and pain levels were measured using the Visual Analog Scale (VAS) before and after treatment. The results showed a consistent decrease in the pain scale. For example, in the active phase with a 6 cm cervical opening, the pain scale drops from 7 to 5. In the transition phase, the pain scale drops from 9 to 8 after the intervention. Aromatherapy was administered 11 times during the delivery process. The continuous obstetric care provided includes pregnancy, childbirth, postpartum period, newborns, and family planning, all of which run without complications. Delivery takes place spontaneously, the baby is born healthy (BB 3600 grams, APGAR 8/9), and the mother chooses injectable contraception at 3 months. In conclusion, the application of lavender aromatherapy within the framework of COC has been shown to be effective in lowering labor pain, increasing comfort, and supporting a positive childbirth experience.